1995
DOI: 10.1161/01.res.76.5.802
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Connexin43, the Major Cardiac Gap Junction Protein, Visualizes the Cellular Network for Impulse Propagation From Sinoatrial Node to Atrium

Abstract: Myocytes are electrically coupled by gap junctions, which are composed of low-resistance intercellular channels. The major cardiac gap junction protein is connexin43 (Cx43). The distribution of Cx43 has been studied by immunofluorescence to visualize the electrical coupling between atrial tissue and sinoatrial node. From modeling studies, this coupling was inferred to be gradual in order to shield the sinoatrial node from the atrial hyperpolarizing influence. The actual Cx43 labeling pattern did not show the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 45 publications
2
40
2
Order By: Relevance
“…As previously described, 12,24 we observed an abundance of well-organized Cx43 in the intercalated discs between atrial myocytes near the CT (Figure 4A). At the interface between the SAN and CT (Figure 4B), bundles of atrial muscle cells that express Cx43 protrude into the SAN.…”
Section: Connexin43supporting
confidence: 85%
“…As previously described, 12,24 we observed an abundance of well-organized Cx43 in the intercalated discs between atrial myocytes near the CT (Figure 4A). At the interface between the SAN and CT (Figure 4B), bundles of atrial muscle cells that express Cx43 protrude into the SAN.…”
Section: Connexin43supporting
confidence: 85%
“…105 Cx43 protein is present on bovine, guinea pig, and human atrial myocytes, 106 -108 with a distinct transitional zone containing interdigitating Cx43-expressing atrial and Cx43-lacking nodal cells at the periphery of the SAN. 45,106,108 Canine and rabbit RA gap junctions contain mainly Cx40 and Cx43 and less Cx45. 39,109 Cx40 expression in the atrium is much stronger than in the ventricle (where it is virtually undetectable) in humans, rabbits, guinea pigs, and mice.…”
Section: Ionic Mechanismsmentioning
confidence: 99%
“…However, our previous data 25 suggest that the densities of major ionic currents in SA node rabbit cells are independent of cell size (membrane capacitance). In addition, accumulating data are available on the presence of (strands of) atrial cells in the SA node of rabbit, 26 guinea pig, 27 bovine, 28 and mouse. 29 In rabbit, we were able to isolate atrial cells from the primary pacemaker region.…”
Section: Regional Differences In Membrane Currentsmentioning
confidence: 99%
“…In rabbit SA node, moving from the primary pacemaker center to the atrium, slowing of diastolic depolarization and increase in upstroke velocity correlates with an overall increase in myofibril density and organization. 4 In detailed immunohistochemical studies in rabbit, 26 guinea pig, 27 bovine, 28 and mouse 29 hearts, it was found that the very center of the node is surrounded by a region in which atrial strands protrude the nodal area. Furthermore, in rabbit SA node, a close apposition of typical nodal cells and cells with a high myofibril density and high degree of organization has been observed by electronmicroscopy.…”
Section: Varying Atrio-sinus Interactionmentioning
confidence: 99%